Heme Oxygenase 1 (HO-1) as an Inhibitor of Trafficking of Normal and Malignant Hematopoietic Stem Cells – Clinical and Translational Implications - Ratajczak, Mariusz Z. (Stem Cell Rev Rep, 2020)
Evidence indicates that bone marrow (BM)-residing hematopoietic stem/progenitor cells (HSPCs) are released into peripheral blood (PB) after administration of pro-mobilizing drugs, which induce a state of sterile inflammation in the BM microenvironment. In the reverse process, as seen after hematopoietic transplantation, intravenously injected HSPCs home and engraft into BM niches. Here again, conditioning for transplantation by myeloablative chemo- or radiotherapy induces a state of sterile inflammation that promotes HSPC seeding to BM stem cell niches. Therefore, the trafficking of HSPCs and their progeny, including granulocytes and monocytes/macrophages, is regulated by a response to pro-inflammatory stimuli. This responsiveness to inflammatory cues is also preserved after malignant transformation of hematopoietic cells. Results from our laboratory indicate that the responsiveness of hematopoietic cells to pro-inflammatory stimuli is orchestrated by Nlrp3 inflammasome. As reported, HO-1 effectively attenuates intracellular activation of Nlrp3 inflammasome as well as the pro-inflammatory effects of several humoral mediators, including complement cascade (ComC) cleavage fragments that promote migration of hematopoietic cells. Based on this finding, inhibition of HO-1 activity may become a practical strategy to enhance the mobilization and homing of normal HSPCs, and, alternatively, its activation may prevent unwanted spread and in vivo expansion of leukemic cells. [Figure: see text]